The Impact of Academic Supervision and Infrastructure Management to Increase the Quality of Junior High School Graduates with Learning Environment as a Mediating Variable - Dwi Yunianto Nugroho; Ruhiat, Yayat; Atikah, Cucu (Universitas Pendidikan Ganesha, 2025)
The educational problem faced by the Indonesian nation is the low quality of graduates at every level of the education system. The low quality of graduates can be seen from the Programme for International Student Assessment (PISA) 2022 results, where Indonesia is ranked 69th out of 80 participating countries. This study aims to analyze the effect of academic supervision competence and infrastructure management on the quality of graduates, with the learning environment as a mediating variable. This study uses a quantitative method, with path analysis, to test exogenous variables' direct and indirect effects on endogenous variables. Sampling using non-probability sampling with purposive sampling technique. The sample taken consisted of 29 principals of public junior high schools. Data collection used a questionnaire instrument with a Likert scale. The data analysis technique used the t-test to test the direct effect and the Sobel test to test the indirect effect of the dependent variable with the independent variable. The study's results showed a significant positive direct effect of academic supervision competence on the quality of graduates. Infrastructure management had a significant positive direct effect on the quality of graduates. There was a significant positive direct effect of the learning environment on the quality of graduates. Academic supervision of graduate quality through the learning environment has an indirect and mediating effect. Management of facilities and infrastructure on graduate quality through the learning environment has an indirect and mediating effect. The implications of this study can be a consideration for principals to implement academic supervision and management of facilities and infrastructure based on the learning environment to improve graduate quality.